2022
DOI: 10.3390/molecules27103240
|View full text |Cite
|
Sign up to set email alerts
|

Stability of ZIF-8 Nanoparticles in Most Common Cell Culture Media

Abstract: Zeolite imidazolate framework-8 (ZIF-8) is a promising platform for drug delivery, and information regarding the stability of ZIF-8 nanoparticles in cell culture media is essential for proper interpretation of in vitro experimental results. In this work, we report a quantitative investigation of the ZIF-8 nanoparticle’s stability in most common cell culture media. To this purpose, ZIF-8 nanoparticles containing sterically shielded nitroxide probes with high resistance to reduction were synthesized and studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…MILs are reported to be non-toxic, biodegradable nanocarriers suitable for antitumoral and retroviral drug delivery, imaging, and minimal in vivo toxicity [ 10 , 11 ]. ZIFs have been reported for drug and biomolecule delivery with demonstrated biocompatibility, biodegradability, protection, and encapsulation properties [12] , [13] , [14] , [15] , [16] . The most current bio-application of MOFs is in the field of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…MILs are reported to be non-toxic, biodegradable nanocarriers suitable for antitumoral and retroviral drug delivery, imaging, and minimal in vivo toxicity [ 10 , 11 ]. ZIFs have been reported for drug and biomolecule delivery with demonstrated biocompatibility, biodegradability, protection, and encapsulation properties [12] , [13] , [14] , [15] , [16] . The most current bio-application of MOFs is in the field of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] It was reported that ZIF-8 shows high chemical stability toward the nitroxide compound. [37] Taking this fact into account, we can deduce that structure of chiral ZIF after full removal of CNCs with nitroxide compound, NMMO • H 2 O, would be same with that of chiral ZIF in the composite film. As can be seen in Figures 2c, 2f to 2h, S9, and S10, the templated grown ZIF has a needle-like morphology with a broad distribution of diameters and lengths around 84 nm and 270 nm, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…Next, pure templated‐grown ZIF can be separated after full removal of the CNCs with N ‐methyl morpholine N ‐oxide monohydrate (NMMO ⋅ H 2 O) from the ZIF‐CNC film (Figures S4 and S5) [35,36] . It was reported that ZIF‐8 shows high chemical stability toward the nitroxide compound [37] . Taking this fact into account, we can deduce that structure of chiral ZIF after full removal of CNCs with nitroxide compound, NMMO ⋅ H 2 O, would be same with that of chiral ZIF in the composite film.…”
Section: Resultsmentioning
confidence: 99%
“…ZIF‐8 belongs to a family of MOFs with a high specific surface area, controllable pore size, functional pores, and a flexible chemical structure [28] and can be used as a host for a wide range of drugs. It has good biocompatibility [29] . Primarily, ZIF‐8 and APTES are used in combination to limit non‐uniform distribution, weak biomolecule interaction, and ion leaching on surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…It has good biocompatibility. [29] Primarily, ZIF-8 and APTES are used in combination to limit non-uniform distribution, weak biomolecule interaction, and ion leaching on surfaces. The surfaces modified by a monolayer of APTESassembled amine molecules increase the nucleation of ZIF-8 and decrease their agglomeration, which leads to enhanced compatibility.…”
Section: Drug Releasementioning
confidence: 99%